Afterword. Issue 5 (3rd September 2022) - Wilson, Ross
ABSTRACT: This afterword begins by taking the final line of Shelley's "Ode to the West Wind" as a motif in order to consider (1) the fate of revolutionary hopes now over two centuries old and (2) categories such as "winter" and "spring" which have been altered as a consequence of climate change. There is brief mention of the various identities that have been ascribed to Shelley in the 200 years since his death before the afterword touches on the prospects for literary critics and scholars today.